ERA-40 Monthly Means of Surface and Flux Forecast Data - European Centre For Medium-Range Weather Forecasts (UCAR/NCAR - Research Data Archive, 2005)
Monthly means of surface and flux forecast data from ECMWF ERA-40 reanalysis project are in this dataset.